Comparisons between swing phase characteristics of race walkers and distance runners - Smith, L. C.; Hanley, B. (International Journal of Exercise Science, 2013)
The aim of this study was to analyze swing characteristics during race walking and to compare these with distance running. The rules of race walking demand that no visible flight time should occur and the stance leg must be straightened from initial contact to midstance. Previous research has not examined whether these rules also have an effect on swing and what consequences might arise. Ten male race walkers and ten male distance runners walked or ran respectively on an instrumented treadmill for 10 km with two in-dwelling force plates. Trials lasted 30 seconds and simultaneous 2D video data were recorded and digitized at 125 Hz. The moment of inertia of the thigh, shank, foot and whole lower limb was calculated using the parallel axis theorem. The distance runners were faster with longer strides, although cadence was not different. The race walkers had shorter swing times, longer contact times, and smaller maximum knee flexion angles (100° ± 6) than the distance runners (56° ± 6). The smaller knee flexion angles in race walkers meant they experienced greater swing leg moment of inertia than the distance runners but there were few associations in either group between knee flexion angle or moment of inertia with key performance parameters. Swing phase kinematics in race walking are restricted by the rules of the event and result in knee angular motions different from those in distance running, preventing race walkers from reaching the speeds attainable by distance runners.